Introduction to mechanics of materials - Riley, William F.; Zachary, Loren W. (New York : John Wiley and Sons, 1989)
This book provides knowledge of the relations between the loads applied to a nonrigid body made of a given material and the resulting deformations of the body, the stresses and strains for a wide variety of conditions and materials...
Keywords: Strength of materials; Structural analysis (Engineering); Strength of materials